Analisis Kesulitan Belajar Siswa Kelas VIII dalam Menyelesaikan Soal Cerita Teorema Pythagoras - Aghna Ikhtiara Hendra Rachman; Auliaul Habibah Rosyidi; Nur Wiji Sholikin (PT Cendekia Education Center, 2026)
This study aims to analyze the learning difficulties of eighth-grade students in solving Pythagorean Theorem word problems using a qualitative approach with a phenomenological case study design involving 19 students at Ummul Quro Junior High School, with an in-depth analysis focusing on six students representing high, medium, and low ability levels. Data were collected through triangulation of three instruments, namely mathematics tests, semi-structured interviews, and questionnaires to identify conceptual, procedural, and spatial visualization difficulties. The results showed that low-ability students experienced fundamental difficulties in spatial visualization (33.3%-41.6%) and identifying the hypotenuse, medium-ability students faced challenges in procedural decision-making, while high-ability students tended to be less careful due to overconfidence despite having high intrinsic motivation (83.3%-91.7%). The findings indicate the need for differentiated learning tailored to the characteristics of difficulties at each ability level, with an emphasis on a concrete-contextual approach for low-ability students, procedural guidance for medium-ability students, and increased accuracy for high-ability students. Keywords: Learning difficulties, Pythagorean theorem, word problems, spatial visualization, differentiated learning